Complications of 90Y Radioembolization Treatment for Liver Tumors - Eghbali, Mason; Haber, Zachary M.; Srinivasa, Ravi N.; Padia, Siddharth A. (Digestive Disease Interventions, 2023)
Y90 radioembolization has been demonstrated to be a safe and effective treatment for patients with HCC and for certain liver metastases, such as neuroendocrine tumors, uveal melanomas, and breast cancer. Although the procedure is relatively safe, the complications associated with radioembolization vary greatly in their locations, presentation, and severity. This review aims to discuss and increase awareness of the potential complications associated with radioembolization.
Keywords: radioembolization; complications; Y90